Emotional Intelligence and Culture Boost Accounting Understanding in Indonesia: Kecerdasan Emosional dan Budaya Meningkatkan Pemahaman Akuntansi di Indonesia - Olivia, Debby; Nurasik (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of learning behavior, interest in learning, emotional intelligence, and culture on the understanding of financial accounting. Despite extensive research on factors influencing academic performance, there remains a gap in understanding how these specific variables affect accounting students' comprehension. The research employs a quantitative approach, analyzing data from 77 accounting students from the 2018 and 2019 cohorts at Muhammadiyah University of Sidoarjo. Data were collected via questionnaires distributed through Google Forms and analyzed using multiple regression analysis with SPSS. Results indicate that while learning behavior and interest in learning do not significantly influence financial accounting understanding, emotional intelligence and culture do. These findings suggest that emotional intelligence and cultural context play crucial roles in academic performance, highlighting the need for educational strategies that enhance these aspects to improve accounting education. Future research should explore the mechanisms through which emotional intelligence and culture affect learning outcomes in different educational settings. Highlight: Emotional intelligence and culture significantly influence accounting understanding. Learning behavior and interest do not affect financial accounting comprehension. Enhancing emotional intelligence and cultural awareness can improve academic performance. Keywoard: Learning Behavior, Interest in Learning, Emotional Intelligence, Culture, Financial Accounting Understanding